Biomimetics: A Biomimetic Composite from Solution Self‐Assembly of Chitin Nanofibers in a Silk Fibroin Matrix (Adv. Mater. 32/2013). (19th August 2013) - Jin, Jungho; Hassanzadeh, Pegah; Perotto, Giovanni; Sun, Wei; Brenckle, Mark A.; Kaplan, David; Omenetto, Fiorenzo G.; Rolandi, Marco
<x xml:space="preserve">Abstract</x> Marco Rolandi, Fiorenzo G. Omenetto, and co‐workers describe a transparent nanofiber biocomposite, self‐assembled from a solution of squid pen chitin and silk fibroin from Bombyx mori cocoon, on page 4482. The microstructure and the mechanical properties are easily tuned by the ratio of the components. Chitin and silk are naturally abundant and biocompatible, applications in naturally derived plastics and biomedical devices may be envisaged. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>